Politics UK government and politics, political ideas, US government and politics - Jefferies, John; Jenkins, Sarra; Tuck, David (Hodder Education, 2023)
- Includes all core and non-core political ideas, with key thinkers integrated throughout the text - Builds confidence by highlighting key terms and explaining links between different topics in the specification - Provides opportunities to test your progress with quick knowledge-check questions. - Develops analysis and evaluation skills with 'stretch and challenge' activities and suggestions for targeted further reading. - Features practice questions with answer guidance online at www.hoddereducation.co.uk.